41 : a portrait of my father - Bush, George W. (George Walker), 1946- (New York : Crown Publishers, 2014)
George W. Bush covers the entire scope of the elder President Bush's life and career, including his service in the Pacific during World War II, his pioneering work in the Texas oil business, and his political rise as a Congressman, U.S. Representative to China and the United Nations, CIA Director, Vice President, and 41st President of the United States.
Beginnings -- War -- Heading West -- Hat in the ring -- Man of the house -- Diplomacy -- Runner-up -- Within a heartbeat -- The road to the White House -- Number 41 -- The hardest year -- The afterlife.
Includes index.
Keywords: Bush, George, -- 1924-2018.; Presidents -- United States -- Biography; United States -- Politics and government -- 1989-1993.